Dyadic Characteristics and Intimate Partner Violence among Men Who Have Sex with Men - Stephenson, Robert (Western Journal of Emergency Medicine, 2011)
Objective: Although the research community has begun to recognize intimate partner violence (IPV) as an important issue in same-sex relationships, there has been a lack of attention to characteristics of these relationships that may be associated with IPV. In particular, there has been a lack of attention paid to the associations between dyadic characteristics and IPV in same-sex relationships. This paper examined associations between dyadic characteristics, including relationship satisfaction, communal coping and efficacy, and perpetrating and experiencing IPV among a sample of United States men who have sex with men (MSM). Methods: We collected data via an online survey with 528 MSM, who were greater than 18 years of age and reported at least one male sex partner in the last 12 months. The analysis examined dyadic factors associated with reporting of experiencing and perpetrating emotional violence, physical violence, and sexual violence. Results: The prevalence of violence in the sample ranged from nine percent reporting perpetrating sexual violence to 33% of men reporting experiencing emotional violence. MSM who reported greater satisfaction with their relationship or who reported a higher degree of concordance with their partner on lifestyle choices were less likely to report experiencing or perpetrating emotional violence. MSM who perceived a stigma to being in a male same-sex couple were less likely to report experiencing or perpetrating sexual violence. Conclusion: The results presented here demonstrate high levels of IPV among MSM and that dyadic characteristics are associated with the occurrence of IPV. Understanding relationship characteristics associated with increased IPV among same-sex male couples can contribute to the development of more accurate IPV screening tools, and more sensitively and appropriately designed intervention messages. [West J Emerg Med. 2011;12(3):324-332.]